Pro-Tanah Papua (Podcast Dan Radio Online Untuk Anak Papua) Sarana Pendidikan Nonformal, Diskusi Dan Informasi Berbasis Local Wisdom Papua - Mukhlas Triono; Endra Putra Raharja; Budi Santoso (Universitas Pendidikan Muhammadiyah Sorong, 2023)
This community service targeting indigenous Papuan youth (hereinafter referred to as KMAP) is currently one of the age levels that is deemed necessary to get more attention, especially in the education sector. The lack of educational and motivational information facilities and the lack of access to foreign news have an impact on information gaps. To convey interesting information, the right media is certainly needed, one of which is podcasts. The PRO-LAND PAPUA Program (Online Podcast and Radio for Papuan Children) aims to be a means of non-formal education and educational information that can provide motivation for indigenous Papuan youth. The method used is with several stages, namely the preparation, implementation and evaluation stages. The PAPUA PRO-LAND program was produced using a local wisdom approach and is packaged in a more millennial way to be closer to KMAP. The resulting video and audio are uploaded to the YouTube channel and can be accessed again at any time. By optimizing partner resources, namely UNIMUDA Campus Radio Sorong Insania FM and the UNIMUDA Sorong Public Relations Team, this community service presents local wisdom-based content that is educational and informative to indigenous Papuan youth.